1975
DOI: 10.1099/00222615-8-2-349
|View full text |Cite
|
Sign up to set email alerts
|

T-Mycoplasmas: A Study of the Morphology, Ultrastructure and Mode of Division of Some Human Strains

Abstract: PLATES XVIII AND XIX RELATIVELY little is known about the gross morphology, mode of division and ultrastructure of the T-mycoplasmas. In stained preparations viewed by light microscopy they appear as uniform, minute coccoid particles, about 0.3 pm in diameter, embedded in a gelatinous matrix (Ford and MacDonald, 1963 ;Shepard, 1967). Fluorescence microscopy after acridine-orange staining indicates that they are rich in RNA and DNA (Shepard, 1967). Electron microscopy (EM) confirmed these observations and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…The structures observed on the outer surface of the zonae pellucidae of nine of the nine embryos experimentally exposed to U. diversum were morphologically identical to the small, granular forms observed in the U. diversum preparation, and those described previously in the early logarithmic phase of ureaplasma growth (27). On the basis of the presence of structures morphologically identical to U. diversum on the zonae pellucidae of all nine embryos exposed to U. diversum strain 2312 and the absence of similar structures on embryos not exposed to the organism, it was concluded that U. diversum strain 2312 attached to the outer surface of the bovine zona pellucida.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The structures observed on the outer surface of the zonae pellucidae of nine of the nine embryos experimentally exposed to U. diversum were morphologically identical to the small, granular forms observed in the U. diversum preparation, and those described previously in the early logarithmic phase of ureaplasma growth (27). On the basis of the presence of structures morphologically identical to U. diversum on the zonae pellucidae of all nine embryos exposed to U. diversum strain 2312 and the absence of similar structures on embryos not exposed to the organism, it was concluded that U. diversum strain 2312 attached to the outer surface of the bovine zona pellucida.…”
Section: Discussionsupporting
confidence: 81%
“…This study illustrates that U. diversum strain 2312 attaches to the outer surface of the bovine zona pellucida, that ureaplasmas do not penetrate the zona pellucida and that the organism does not cause morphological changes in bovine morulae following 16 hours incubation in vitro. The cellular morphology of U. diversum strain 2312 is identical to that described previously for U. urealyticum and U. diversum (24,25,26,27,28).…”
Section: Discussionsupporting
confidence: 71%
“…A further observation from the SEM images was the presence of budding and potentially the formation of membrane vesicles. Budding has previously been observed among ureaplasmas, but little is known with regards to the formation of membrane vesicles (Whitescarver and Furness 1975). Finally, from the SEM images, structures which resembled suspected conjugation pili were apparent.…”
Section: Discussionmentioning
confidence: 76%
“…The replication mode of M. salivarium in the epithelial cells was confirmed to be by equal or unequal binary fission by images showing invagination of membranes and formation of a cross-septum, when using the ultracryotomy immunolabeling method. A previous study that investigated the cell division of T-Mycoplasma by EM reported that invagination of bound membrane was seen, but no cross-septum was seen (Whitescarver and Furness, 1975 ). In this study, both invagination and cross-septum formation were observed.…”
Section: Discussionmentioning
confidence: 97%